1997
DOI: 10.1111/j.1471-0528.1997.tb11464.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral misoprostol in the prevention of postpartum haemorrhage

Abstract: Objective To investigate the use of the oral prostaglandin E, analogue, misoprostol in the prevention of Design A prospective observational study.Setting A university teaching hospital. Participants Two hundred and thirty-seven consecutive women undergoing vaginal delivery.Methods All the women were given 600 pg oral misoprostol just after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 25 publications
5
70
1
1
Order By: Relevance
“…In disagreement with the present outcome, some research work had indicated cases of diarrhoea (3%) in misoprostol group [13,17,18]. In another twist, El-Refaey et al (2000) reported significantly higher incidences of nausea in misoprostol medication group than in standard oxytocics.…”
Section: Discussioncontrasting
confidence: 75%
“…In disagreement with the present outcome, some research work had indicated cases of diarrhoea (3%) in misoprostol group [13,17,18]. In another twist, El-Refaey et al (2000) reported significantly higher incidences of nausea in misoprostol medication group than in standard oxytocics.…”
Section: Discussioncontrasting
confidence: 75%
“…The difference was statistically significant between rectal misoprostol and IM 15methyl-PGF2α group (p< 0.001) and also between oral misoprostol and rectal misoprostol group (p=0.041). The findings were comparable to El Refaey et al study 27 .…”
Section: Nauseasupporting
confidence: 82%
“…Following earlier uncontrolled reports 2,3 of misoprostol use during the third stage of labour, a large multicentre trial was conducted by WHO to evaluate the effectiveness of 600 Ag misoprostol compared with 10 IU of oxytocin 4 . This large randomised controlled trial and a systematic review of seven randomised controlled trials 5 demonstrated that 10 IU of oxytocin (im or iv) is preferable to 600 Ag misoprostol given orally in the active management of the third stage of labour in hospital settings where active management is the norm.…”
Section: Introductionmentioning
confidence: 99%